A Sensitivity Study on the Soil Parameter-Boundary Layer Height Interrelationship. (3rd June 2012) - Breuer, Hajnalka; Ács, Ferenc; Horváth, Ákos; Laza, Borbála; Matyasovszky, István; Németh, Péter; Weidinger, Tamás; Rajkai, Kálman
Abstract : Simulations with the WRF model have been carried out with high resolution soil data to analyze its effect on planetary boundary layer (PBL) development. The default soil texture distribution of 5 ′ horizontal resolution has been replaced with a 30 ′′ one on the basis of the Digital Kreybig Soil Information System and Hungarian Agrogeological Database in Hungary. Soil parameter values determined from HUNSODA and MARTHA Hungarian soil databases were also compared. Comparison of PBL height simulations and measurements obtained by radiometer and windprofiler shows that the impact of soil parameter differences on PBL height evolution is not negligible. The latent heat flux and PBL height daytime courses show significant (P < 0.01 ) differences over more than 50% of the model domain covering the Carpathian basin.